2012
DOI: 10.1530/rep-11-0438
|View full text |Cite
|
Sign up to set email alerts
|

FKBP4 is regulated by HOXA10 during decidualization and in endometriosis

Abstract: FKBP4 (FKBP52) and FKBP5 (FKBP51) are progestin receptor (PR) co-chaperone proteins that enhance and inhibit, respectively, progestin-mediated transcription by PR. Here, we examined FKBP4 and FKBP5 expression in the eutopic endometrium of fertile women with endometriosis and effects of FKBP4 and FKBP5 on the decidualization of human endometrial stromal cells (HESCs), and assessed HOXA10 regulation of FKBP4. Expression of FKBP4 mRNA was increased in the late proliferative phase and remained elevated throughout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 41 publications
1
39
1
2
Order By: Relevance
“…* P<.05 versus without RU486. (24,25). In addition, decidualization was greater when EuSC were treated with drospirenone and E 2 than with drospirenone alone, which suggests that the expression of P receptors was up-regulated by E 2 (26,27) and that the P receptor agonistic effect of drospirenone may be enhanced.…”
Section: Figurementioning
confidence: 94%
“…* P<.05 versus without RU486. (24,25). In addition, decidualization was greater when EuSC were treated with drospirenone and E 2 than with drospirenone alone, which suggests that the expression of P receptors was up-regulated by E 2 (26,27) and that the P receptor agonistic effect of drospirenone may be enhanced.…”
Section: Figurementioning
confidence: 94%
“…This impaired E metabolism, coupled with the abnormal high expression of P450 aromatase that is seen in endometriotic tissue, leads to excessive local E signaling, which presumably drives the growth of endometriotic lesions. Additional studies have linked impaired expression of other key P-regulated pathways in the stroma to the pathogenesis of endometriosis (105)(106)(107). Bulun's group has also reported that the level of ESR2 expression is significantly greater in endometriotic stroma vs normal (108).…”
Section: Dysfunction Of Stromal-epithelial Crosstalk Leads To Reprodumentioning
confidence: 99%
“…FKBP52 has been shown to be decreased in endometriosis. 167,168 This PR chaperone protein is required for proper progesterone-mediated actions and its reduction in this disease may be a major determinant in progesterone resistance. 136 …”
Section: Endometriosis: a Complex Disease For Which Improved Treatmenmentioning
confidence: 99%